Household consumption and labour participation in Nigeria: Survey-based evidence - Bula, Yunah B; Sani, Mohammed A; Aliyu, Victoria O; Inusa, Eshiozemhe M; Dogo, Bishara S (Asian Development Policy Review, 2023)
Labour participation is a vital component of economic development because of its significance in influencing the well-being of individuals in an economy. As a result, this paper investigated how labour participation influences household consumption in the developing country of Nigeria. For simplicity, the paper used only the labour participation of the head of the household as a proxy for the labour participation of the whole household. The study made use of data extracted from the Nigerian Living Standard Survey (NLSS) carried out in 2018–2019 by the National Bureau of Statistics in conjunction with the World Bank. The data was analysed using descriptive statistics, linear regression, and logit models. The results showed that households whose head is self-employed consume less than those whose heads are unemployed, while households whose heads are employed consume significantly more than those whose heads are unemployed. The outcome for the self-employed contradicts the notion that unemployed household heads are likely to consume less than self-employed household heads.